2021
DOI: 10.22541/au.161051252.26168891/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids supplementation improve clinical symptoms in patients with covid-19: A randomized clinical trial

Abstract: Objective: We hypothesized that omega-3 fatty acids would be an appropriate adjunct therapy for alleviating the inflammatory response and clinical manifestation in hospitalized patients with covid-19 disease. Methods: This was a single-blind randomized controlled trial in Amir-Alam hospital in Tehran. Thirty adult men and women diagnosed with covid-19 were allocated to either control group (receiving Hydroxychloroquine) or intervention group (receiving Hydroxychloroquine plus 2 grams of DHA+EPA) for 2 weeks. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The recent VASCEPA-COVID-19 CardioLink-9 trial showed that oral n-3 PUFA treatment with the EPA ethyl ester icosapent ethyl for 14 days improves symptoms and reduces C-reactive protein (CRP) in ambulatory COVID-19 patients [ 15 ]. Similar results have been reported in a smaller studies of n-3 PUFA added to hydroxychloroquine-treatment of COVID-19 (performed at the time it was used) [ 16 ] and in critically ill COVID-19 patients [ 17 ]. However, no previous study has examined the relation of beneficial effects of n-3 in relation to OS in patients with COVID-19.…”
Section: Introductionsupporting
confidence: 87%
“…The recent VASCEPA-COVID-19 CardioLink-9 trial showed that oral n-3 PUFA treatment with the EPA ethyl ester icosapent ethyl for 14 days improves symptoms and reduces C-reactive protein (CRP) in ambulatory COVID-19 patients [ 15 ]. Similar results have been reported in a smaller studies of n-3 PUFA added to hydroxychloroquine-treatment of COVID-19 (performed at the time it was used) [ 16 ] and in critically ill COVID-19 patients [ 17 ]. However, no previous study has examined the relation of beneficial effects of n-3 in relation to OS in patients with COVID-19.…”
Section: Introductionsupporting
confidence: 87%